Associative potential of anthroponyms in ukrainian political discourse - Gapchenko, Olena (Ukrainian linguistics, 2022)
This article is devoted to an experimental study of the associative potential of anthroponyms in Ukrainian political discourse. We turned to a free-associative experiment in order to study the status of anthroponyms in political communication, as well as to reveal their associative potential. The results were interpreted using statistical and typological data processing, along with the methods of component analysis, cognitive modeling, etc. As words-stimulus, we used the names of domestic and foreign politicians from different periods known to modern speakers (not only to specialists in the field of politics and journalists but also to the general public) – no matter the ambiguous attitude of the society toward them and their activities. The experiment participants were representatives of different regions of Ukraine, of different ages, levels of education, and professions. The main object of the analysis was the associative reactions of the speakers obtained during the experiment. The main focus was on studying the semantic specifics of anthroponyms, associative connections, and the peculiarities of the functioning of these units in political communication.The experiment results showed a significant associative potential of the anthroponyms in political discourse, determined by objective and subjective factors. Those associations that have to do with the anthroponyms-names of famous Ukrainian and foreign politicians of different periods convey essential background knowledge of speakers and determine the semantics and pragmatics of these units. Most often, in associative reactions to anthroponymic stimuli, we can trace such denotative characteristics as a politician’s field of activity, the historical period in question, place of activity, nationality, appearance, character traits, intelligence, behavioral features, and other typical features. Furthermore, anthroponyms cause connotative reactions. Experimental studies prove that anthroponyms have, although somewhat specific, yet rich semantics and form a part of the process of encoding and decoding information. Information about the author:Olena Gapchenko – PhD, Associate Prof. of the Department of the Ukrainian Language and Applied Linguistics; Educational and Scientific Institute of Philology; Taras Shevchenko National University of Kyiv (Ukraine).E-mail: olenagapchenko@ukr.net__________References• Baranov, A. N., Kazakevich, E. G. (1991). Parlamentskie debaty: traditsii i novatsii. Moskva: Znanie, 64 p. (in Russian).• Deik, T. A. van. (1989). Yazyk. Poznanie. Kommunikatsiya. Moskva : Progress, 310 p. (inRussian).• Karasik, V. I. (2000). O tipakh diskursa. Yazykovaya lichnost’: institutsional’nyi i personal’nyi diskurs, V. I. Karasik, G. G. Slyshkin (eds.). Volgograd : Peremena, 5–20 (inRussian).• Reformatskii, A. A. (2001). Vvedenie v yazykovedenie. Moskva : Aspekt Press, 536p. (in Russian).• Romanov, A. A. (2002). Politicheskaya lingvistika. Funktsional’nyi podkhod. Moskva–Tver’ : IYa RAN, TvGU, 191 p. (inRussian).• Ufimtseva, A. A. (2010). Leksicheskaya nominatsiya (pervichnaya neitral’naya). Moskva : Knizhnyi dom “LIBROKOM”, 88 p. (inRussian).• Sheigal, E. I. (2004). Semiotika politicheskogo diskursa. Moskva : ITDGK “Gnozis”, 326p. (in Russian).• Sorensen, H. S. (1963). The meaning of proper names. With a difiniens formula for proper names in modern English. Copenhagen : Gad, 116p. (in English).
Keywords: political discourse, political communication, personal name, anthroponym, associative potential, precedent phenomenon